The Anthropologist and the Article - Reid, Bill (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1984)
For some reasons, most of the people, particularly anthropologists who write about the supernatural creatures of the Pacific Northwest Coast mythology, employ, to my way of thinking, a most peculiar dictional device: the dropping of the article which should ordinarily precede their specific names: e.g. “Raven” instead “the raven”. I have always found this practice most irritating and was eventually driven to write this paper. In doing so, I may have discovered that my argument goes deeper than a mere matter of style and touches on something fundamental regarding the attitude of today’s society to tribal peoples and their cultures.